1995
DOI: 10.1007/bf00569568
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic dysfunction is not related to changes in glycaemic control over 6 months in type 2 (non-insulin-dependent) diabetes mellitus

Abstract: Diastolic dysfunction may be the earliest marker of a diabetes-induced heart muscle disease which leads to the progressive development of cardiac failure. Left ventricular diastolic function was indirectly assessed using pulsed wave Doppler ultrasound mitral-flow velocities in 20 normotensive patients with a new diagnosis of type 2 diabetes mellitus, normal cardiac function and no evidence of coronary artery disease and in 16 age-matched normal subjects. Peak velocities of early (E) and late (A) left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…13 However, other studies have demonstrated no significant association between glycemic control and cardiac function. [21][22][23][24][25] The lack of correlation between systolic and diastolic function with HbA1c at baseline in our patients may have been because of by guest on May 9, 2018 http://circimaging.ahajournals.org/ Downloaded from the selection criteria: our patients were selected into the study as they all had poor glycemic control.…”
Section: Systolic and Diastolic Function In Diabetes Mellitusmentioning
confidence: 96%
“…13 However, other studies have demonstrated no significant association between glycemic control and cardiac function. [21][22][23][24][25] The lack of correlation between systolic and diastolic function with HbA1c at baseline in our patients may have been because of by guest on May 9, 2018 http://circimaging.ahajournals.org/ Downloaded from the selection criteria: our patients were selected into the study as they all had poor glycemic control.…”
Section: Systolic and Diastolic Function In Diabetes Mellitusmentioning
confidence: 96%
“…In addition to revealing a prevalence of LVDD of Ͼ50%, this study also unmasked a significant number of subjects (28%) with a pseudonormal pattern of diastolic filling that has yet to be recognized in previous studies (4)(5)(6)(7)(8)(9)(10)(11). In these studies, the Valsalva maneuver and pulmonary venous recordings were not used.…”
Section: Transmitral and Pulmonary Venous Doppler Flow Velocity Recormentioning
confidence: 99%
“…However, other studies have found no such correlation (4,6,11,18). It has been suggested that LVDD is secondary to microvascular disease because an association with retinopathy has been described (7,8).…”
mentioning
confidence: 98%
“…Diabetic cardiomyopathy is characterized by an early diastolic dysfunction and a late systolic one, with intracellular retention of calcium and sodium and loss of potassium. The mechanism of diastolic dysfunction remains unknown, but it does not appear to be due to changes in blood pressure, microvascular complications, or elevated circulating glycated hemoglobin levels (15,16). We tested whether the impairment of cardiac function in diabetes is dependent upon the activation of the PARP pathway within the heart.…”
mentioning
confidence: 99%